Harry Potter and the sorcerer's stone - Rowling, J. K. (New York : A.A. Levine Books, 1998)
Rescued from the outrageous neglect of his aunt and uncle, a young boy with a great destiny proves his worth while attending Hogwarts School for Witchcraft and Wizardry.
Keywords: Fantasy -- Fiction; Witches -- Fiction; Wizards -- Juvenile fiction; Schools -- Fiction; Potter, Harry (Fictitious character) -- Juvenile fiction; England -- Juvenile fiction